UPAYA MENINGKATKAN KREATIVITAS DAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN ORIGAMI DI KELAS B TK AISYIYAH BUSTANUL ATHFAL LEDUG KECAMATAN KEMBARAN KABUPATEN BANYUMAS JAWA TENGAH - Supriati, Supriati (CV Sintesia, 2024)
Motor is the development of controlling body movements through coordinated activities between the nervous system, muscles, brain and spinal cord. Therefore, early childhood needs to be stimulated through exercise to help physical and spiritual growth and development. The purpose of this study was to determine the increase in creativity and fine motor skills through morigami. Classroom action research was carried out in class B Kindergarten aisyiyah ba ledug in 2 cycles. Each cycle is carried out for 5 days. Cycle 1 will be held on 6 -10 September 2021 and cycle 2 will be held on 13-17 September 2021. The results showed an increase in learning outcomes from the initial study to cycle 1 and from cycle 1 to cycle 2 which was quite significant. In cycle 1, children's ability in learning origami reached 75% and increased in cycle 2, which reached 93.75%. Meanwhile, in children's creativity in origami, in cycle 1 it reached 37.5%. And increased in cycle 2 which is 75%. From this learning research, it is suggested to Kindergarten Aisyiyah Ba Ledug and Kindergarten teacher to Tk Aisyiyah Ba Ledug that to improve fine motor skills and creativity, origami can be done.